Mapping of Javanese subdialects in Cirebon and Indramayu - Efendi, Irfan; Gloriani, Yusida; Kanijah, Kanijah; Hasanudin , Cahyo; Nusantara, Liga Alhaqi Audi Putra (BAHASTRA, 2025)
This study aims to identify and map the subdialects of Cirebon-Indramayu Javanese based on word/phrase forms and their meanings, and to analyze their dialectal relationships. This study is a sociolinguistic study, using a direct method (field survey), which involves collecting data by directly visiting respondents. Based on the research findings, there are 57 dialectal vocabulary items from Cirebon-Indramayu Javanese originating from four sub-districts in Cirebon Regency and six sub-districts in Indramayu Regency: Gegesik, Susukan, Kapetakan, and Tukdana (Cirebon Regency), and Kedokanbunder, Kertasemaya, Krangkeng, Sakagumiwang, Sindang, and Balongan (Indramayu Regency). Based on the results of the vocabulary and meaning study of the 57 vocabularies, 4 subdialects of Cirebon Javanese and 6 subdialects of Indramayu Javanese were identified and mapped, namely the Cirebon dialect: (1) Gegesik subdialect; (2) Susukan subdialect; (3) Kapetakan subdialect; and (4) Tukdana subdialect. The subdialects for Indramayu Javanese are: (1) Kedokanbunder subdialect; (2) Kertasemaya subdialect; (3) Kerangkeng subdialect; (4) Sakagumiwang subdialect; (5) Sindang subdialect; and (6) Balongan subdialect. The Javanese subdialects in several areas in Cirebon and Indramayu are proven to have quite significant differences and contain elements of absorption from Javanese and Sundanese dialects.